Realizing the demand-driven paradigm in vocational education: A case study on vocational high school teaching-industry partnership program - Yuyun Estriyanto (Jurnal Pendidikan Vokasi, 2021)
The teaching-industry partnership program between schools and industry could be a good alternative to be implemented in vocational education. This research aims to describe the collaboration pattern between Vocational High School (VHS) and its industry partner. This research was conducted using the case study qualitative research method. The data were collected through in-depth interviews, observations, and documentation. The informants were teachers, the head of the motorcycle-technician department, trainers from the industry, and senior technicians of the motorcycle maintenance workshop selected based on purposive sampling. The results show that in order to operate well, the program requires: 1.) A close relationship between the school and the industry; 2.) Agreement to share knowledge, skills, equipment, and funding between the two parties; and 3.) The willingness of the school to integrate industrial specificity into the learning system. This study also finds that the program just partially aligned with the demand-driven paradigm. Conformity has been realized in terms of preparing graduates' competence following the industry's need, but not yet in terms of the number of graduates required by the company. Any method in increasing the conformity between the labor demand and supply still needs further study